Improved mesophilic anaerobic digestion of swine wastewater by ammonia stripping with microwave irradiation. Issue 5 (23rd February 2023) - Liu, Yu-Chen; Kang, Jang-Hyun; Ahn, Johng-Hwa
ABSTRACT: Ammonia (NH3 ) stripping by microwave irradiation was used to increase the efficiency of anaerobic digestion. The effects of final temperature ( FT ) (80 ≤  FT  ≤ 100°C) and microwave irradiation time ( MIT ) (2.5 ≤  MIT  ≤ 5.5 min) of NH3 stripping, and hydraulic retention time (HRT) (7 ≤ HRT ≤ 20 d) in anaerobic digester were quantified. NH3 concentration decreased from 2794 to 140 mg/L within 5.5 min at FT  = 100°C. The highest cumulative biogas production (>1800 mL/L) and efficiency of volatile solid removal (> 68%) were achieved at FT  = 100°C and MIT  = 5.5 min. The removal efficiency of volatile solid in digesters fed with untreated swine wastewater (control) and swine wastewater treated by NH3 stripping decreased as HRT decreased. The highest relative improvement of properties compared to the control occurred at 10 or 15 d HRT. Increases in biogas production compared to the control increased with the NH3 stripping as HRT was reduced to 10 d (243% higher at 10 d). The methane content of the produced biogas was 64–69% for control and 68–75% with NH3 stripping in the range of 10–20 d HRT. NH3 stripping using microwave irradiation is an effective pretreatment to improve the anaerobic digestion of swine wastewater. GRAPHICAL ABSTRACT: UF0001